2012
DOI: 10.2131/jts.37.871
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotoxic effect of subchronic exposure to <i>S</i>-(1,2-dichlorovinyl)-<i>L</i>-cysteine in mice

Abstract: -The effect of subchronic exposure of S-(1,2-dichlorovinyl)-L-cysteine (DCVC), an active metabolite of trichloroethylene (TCE), was investigated in mice, as a part of mechanistic assessment of renal toxicity of TCE. To examine the subchronic effects of DCVC on kidney function, Balb/c male mice were administered DCVC orally and intraperitoneally once a week for 13 weeks at 1, 10 and 30 mg/kg (Main Study) and for 8 weeks at 30 mg/kg (PCR Study). At the terminal sacrifice, mice orally and intraperitoneally admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Importantly, DCVC stimulated IL-6 release from HTR-8/SVneo cells to a magnitude comparable to that observed with treatment with the positive control LPS, a strongly immunogenic stimulus. Although there has been little research of DCVC-induced IL-6 release, our findings are consistent with those of a report that DCVC exposure stimulates IL-6 release and increases renal Il6 mRNA expression in mice [14]. Because growing evidence links improper activation of inflammatory pathways including IL-6 with impaired trophoblast function and poor placental development [19], our results suggest that innate immune response activation may be a mechanism by which DCVC can lead to adverse birth outcomes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Importantly, DCVC stimulated IL-6 release from HTR-8/SVneo cells to a magnitude comparable to that observed with treatment with the positive control LPS, a strongly immunogenic stimulus. Although there has been little research of DCVC-induced IL-6 release, our findings are consistent with those of a report that DCVC exposure stimulates IL-6 release and increases renal Il6 mRNA expression in mice [14]. Because growing evidence links improper activation of inflammatory pathways including IL-6 with impaired trophoblast function and poor placental development [19], our results suggest that innate immune response activation may be a mechanism by which DCVC can lead to adverse birth outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…DCVC stimulates formation of reactive oxygen species (ROS) in human kidney proximal tubular cells in vitro, which is blocked by treatment with antioxidants [13]. Additionally, in vivo exposure to DCVC in mice increases levels of proinflammatory cytokines, including interleukin-6 (IL-6) in blood plasma, and stimulates increased mRNA expression of tumor necrosis factor-α (TNF-α), IL-6, and cyclooxygenase-2 in the kidney [14]. …”
Section: Introductionmentioning
confidence: 99%
“…EPA 2011). The mechanistic and animal data that strengthens human evidence for the increased risk of renal cell carcinoma associated with exposures to TCE includes observations of an increase in kidney cancer incidence in male rats (National Toxicology Program 1988; National Toxicology Program 1990), qualitative similarities in TCE metabolism between rodents and humans (Chiu et al 2006), genotoxic and mutagenic properties of glutathione (GSH)-conjugated metabolites of TCE (Moore and Harrington-Brock 2000), and nephrotoxicity observed in mice treated with GSH conjugation metabolites (Shirai et al 2012). Overall, evidence suggests that S -(1,2-dichlorovinyl)-L-cysteine (DCVC), or its downstream reactive electrophile metabolites, may be responsible for kidney tumors in humans by a mutagenic MoA, as well as an MoA that involves cytotoxicity and compensatory cell proliferation (Rusyn et al 2014).…”
Section: Introductionmentioning
confidence: 96%
“…If DCVC was noncytotoxic, it could potentially be used as the tool for delivering drugs to cartilage. However, TCE and DCVC are reportedly strong cytotoxicity (Cummings and Lash, 2000;Davis and Petry, 1994;Lash et al, 2014;Lash et al, 2001;Maltoni et al, 1988;Shirai et al, 2012;Wolfgang et al, 1990;Xu et al, 2008). Our previous study (Takamoto et al, 2008) also showed that the TCE metabolite DCVC significantly reduced the viability of chondrogenic cells ATDC5 at a concentration of 10 μM.…”
Section: Discussionmentioning
confidence: 77%
“…Current understanding of the mechanism of DCVC-induced renal injury derives primarily from studies on isolated proximal tubular cells (Cummings and Lash, 2000;Lash et al, 2014;Xu et al, 2008) or subcellular fractions of renal cortical homogenates from rats, rabbits, and other non-human mammals (Davis and Petry, 1994;Lash et al, 2001;Wolfgang et al, 1990). We also reported subchronic nephrotoxic effects of DCVC in mice (Shirai et al, 2012). Furthermore, we demonstrated that DCVC adversely affects the proliferation and differentiation of cultured osteoblasts, osteoclasts, and chondrocytes (Takamoto et al, 2008).…”
Section: Introductionmentioning
confidence: 76%